“Material de viso construcción para el desarrollo motriz fino de los niños de Educación Inicial II” - Lema Sánchez, Erika Alexandra (2024)
The present project aimed to reinforce the development of visuoconstructive praxias for the enhancement of fine motor skills in children in Early Childhood Education, sub-level 2 of the Educational Unit "Luis Fernando Ruiz", through the use of didactic materials. It was evidenced that the children do not have good eye-hand coordination, hence it was established that they have deficiency in the fine motor area. The methodology proposed was the qualitative approach, executed under descriptive research and bibliographic research. The method employed is inductive, and the techniques used are direct observation and interview. The instruments applied were observation sheets and a guide of open questions. The observation sheet was applied to the 25 children of the aforementioned Educational Unit, and the interview was conducted with the responsible teacher to measure the level of knowledge regarding the use of didactic materials for the consolidation of visuoconstructive praxias. Based on the results obtained from the diagnosis, it was proposed to design a manual of activities for fine motor development, with the respective didactic material, thus strengthening the skills and abilities of the children. The selected visuoconstruction material is suitable for the development of fine motor skills, as it promotes creativity and imagination, effective problem-solving skills, agility in mathematical activities, and strengthens the cognitive, motor, and social areas of the child, thus helping to explore different forms, colors, and textures, giving space for children to experiment and create their own knowledge.